Biomimetic Total Syntheses of Amorfrutins A, B, (S)‐D and (R)‐D and Formal Synthesis of Amorfrutin C. Issue 17 (6th May 2021) - Mies, Thomas; Patel, Calum; Parsons, Philip J.; Barrett, Anthony G. M.
Abstract: Bibenzyl natural products, such as the amorfrutins, contain a heavily substituted aromatic core and display a diverse range of biological activities (anti‐tumor, anti‐diabetic, antimicrobial, and antibiotic). In this study, we report unified syntheses of amorfrutin A to D either through total or formal synthesis by employing a dual biomimetic strategy of polyketide aromatization followed by remote terpene functionalization. The key core structures were synthesized from β‐keto dioxinone esters through a magnesium(II) mediated regioselective C‐acylation, palladium catalyzed decarboxylative allylic rearrangement, and dehydrative cyclization. Abstract : The formal and total biomimetic syntheses of amorfrutin A, B, C and both enantiomers of amorfrutin D are reported through a unified method from a common precursor prepared using a polyketide aromatization reaction.